1994
DOI: 10.1063/1.112104
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-impedance effect in amorphous wires

Abstract: Recent experiments have discovered a giant magneto-impedance (MI) effect in FeCoSiB amorphous wires. This effect includes a sensitive change (as much as 60%) in a high frequency wire voltage by an applied dc magnetic field and is thus a high frequency analog of giant magnetoresistance. We consider this phenomenon in terms of ac complex resistance or impedance. The giant MI effect is demonstrated to arise from a combination of a skin effect and a strong field dependence of the circumferential magnetic permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
517
2
10

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 958 publications
(538 citation statements)
references
References 6 publications
9
517
2
10
Order By: Relevance
“…Circular domain structure with high circumferential permeability proved to be very favorable for the highest GMI effect [1][2]. Such domain configuration is typical for the nearly-zero magnetostrictive amorphous wires mainly produced by Japanise company Unitika LTD [1][2][3].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Circular domain structure with high circumferential permeability proved to be very favorable for the highest GMI effect [1][2]. Such domain configuration is typical for the nearly-zero magnetostrictive amorphous wires mainly produced by Japanise company Unitika LTD [1][2][3].…”
Section: Introductionmentioning
confidence: 92%
“…Such domain configuration is typical for the nearly-zero magnetostrictive amorphous wires mainly produced by Japanise company Unitika LTD [1][2][3]. On the other hand, these amorphous wires with vanishing magnetostriction constant present best magnetic softness [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel magnetic phenomenon has recently received attention by both its basic and technological interests, the magnetoimpedance (MI) effect [1,2]. This phenomenon involves the impedance response of a magnetic material submitted (451) to an ac current of high frequency (1 kHz-1 MHz) and low amplitude (irms < 40 mA).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in GMI was initiated in the early nineties when Panina et al 2 and Beach et al 6 reported a very large effect in amorphous ferromagnetic FeCoSiB wires at small magnetic fields and at relatively low frequencies. Since then, the GMI effect has been investigated in a variety of Fe-and Co-based amorphous ribbons, [7][8][9][10][11] films, [12][13][14] , wires and polycrystalline oxides [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%